Effects of dry needling in lower extremity myofascial trigger points: systematic review - Iqra Khan; Ashfaq Ahmad; Ashfaq Ahmed; Samreen Sadiq; Hafiz Muhammad Asim (Journal of the Pakistan Medical Association, 2021)
Objective: This systematic review was conducted to explore the current evidences on effects of trigger point dry needling as a treatment strategy on pain and range of motion among the subjects with lower extremity myofascial trigger areas. Methods: A systematic review was performed and searched databases including Cochrane Library, PubMed, SPORTDiscus and PEDro. PRISMA guidelines were followed. Inclusion and exclusion of studies were made according to PICOS format. Ten studies were recruited for assessment based on eligibility. Cochrane Risk of Bias tool was used to assess the Randomized and Non-Randomized controlled trials and the methodological assessment was also performed using PEDro 10-point scale. Data synthesis was performed by Vote Counting Method as a descriptive tool. Results: Seven of the total ten studies deemed High score on PEDro and three were scored Fair on the scale. Each of the ten studies documented improvement in the pain over time with the dry needling strategy. None of the studies targeted the other outcomes like anxiety and sleep disturbances related with myofascial trigger points. Conclusion: On basis of the best evidences available dry needling seems to be effective in pain reduction related to lower extremity myofascial trigger points. Evidence also suggests that there is not much positive effect of myofascial trigger point dry needling on depression, anxiety, muscular strength and quality of life. Keywords: Acupuncture therapy, Dry Needling, Lower extremity, Myofascial trigger points Continuous....